Effect of 4 doses of Indole butyric acid and types of cutting on the rooting of sacha inchi (Plukenetia volubilis L.) - Ruiz-Solsol, Henry (2010)
Plukenetia volubilis, known as sacha inchi (Inca’s peanuts) is a climbing, perennial plant native to the Peruvian Amazon. Its seeds are rich in protein and high quality oil, important in human nutrition and applications in health, cosmetics and medicine. The lack of reliable methods for clonal propagation has limited the establishment of plantations and its use at industrial level. The objective of this study was to evaluate the effect of four doses of indole butyric acid (0.00; 0.10; 0.15 and 0.20%) and three types of cutting (basal, middle and apical) on the rooting of juvenile cuttings of sacha inchi using non-mist propagators. The trial was conducted in the nursery of the Peruvian Amazonian Research Institute (IIAP) in San Martin, Peru, using a completely randomized design (DCA) with 4 x 3 factorial arrangement with 3 replications and 9 cuttings per experimen-tal unit. After 30 days, intermediate and basal cuttings rooting showed higher rooting (78.70 and 77.78%), root number (19.21 and 15.75) and major root length (4.07 and 4.24 cm). AIB application was essential to stimulate rooting in this species. The highest rooting percentage (92.59 and 87.65%), root number (25.94 and 20.05) and major root length (4.25 and 4.57 cm) were obtained when IBA at 0.15 and 0.20% was applied. We conclude that it is possible to propagate sacha inchi over (80% rooting) by cuttings if intermediate and basal cuttings are treated with 0.15-0.2% IBA.